Estudio de la preñadilla en su hábitat natural en el barrio Rumipamba de las Rosas, cantón Salcedo, provincia de Cotopaxi. - Medina Pacheco, Alejandro Gerardo (2023)
This research study was carried out in San Miguel Parish, Salcedo Canton, Cotopaxi Province with the purpose of determining the population distribution of the Andean catfish (preñadilla) in its habitat. Seventy-two specimens captured in three capture zones established throughout the study site were used by stratified random sampling. The variables of the captured Andean catfish (preñadillas) were evaluated (visits made, captures by area, size, sex, and external anatomical characteristics), which were analyzed using manual techniques. The results of these data were set out in figures and tables for better interpretation. The visits showed that the catches by zone indicated that zone 2 was the best in terms of catches, males were the most numerous compared to females, and the medium size (5-8 cm) was the most observed. In the evaluation of the natural environment, the pollutants observed were clearly of human origin, the flow measurement showed 5.14 (m3/s), all the fauna was domestic, most of the flora was native and few introduced species were fig trees (ficus carica) being the most representative, both the physical and chemical analysis of the water showed results within the normal ranges established in the ISO norms. The conclusion is that the spring is home to a healthy population of wild Andean catfish (preñadilla), and the aquatic ecosystem is balanced and healthy, using this information can be replicated through a proposal for a conservation management plan to improve the vulnerable condition of the Andean catfish (preñadilla) and improve environmental ethics.